Closed‐Form Expressions of Seismic Deformation in a Homogeneous Maxwell Earth Model. Issue 7 (13th July 2018) - Tang, He; Sun, Wenke
Abstract: Earthquake activities involve coseismic and postseismic deformations, and these seismic deformations can be computed using corresponding dislocation theories. However, conventional dislocation theories are usually given using numerical dislocation Love numbers and numerical Green's functions. In this study, we present explicit expressions of the time‐dependent dislocation Love numbers for a point source in a homogeneous viscoelastic (Maxwell rheology) spherical Earth model and the displacement Green's functions. Other surface variables, such as tilt and strain, can be obtained in a similar manner. The analytical Green's functions are derived from the degenerate deformation system without considering self‐gravitation. The Green's functions can be applied to efficiently compute viscoelastic seismic and volcanic deformations in an approximate manner. Key Points: A fully analytical scheme for seismic deformation using Green's functions is presented The explicit expressions of postseismic Love numbers and Green's functions are presented for point sources in a homogeneous Maxwell Earth model The effect of self‐gravitation on coseismic deformation is negligible